Variability of the nucleolus organizer regions and the presence of the rDNA genes in the supernumerary chromosome of Akodon aff. arviculoides (Cricetidae, Rodentia) - Yonenaga-Yassuda, Yatiyo; De Fátima Lima De Assis, Maria; Kasahara, Sanae [UNESP] (Firenze University Press, 1992)
The distribution of Ag-NORs was analyzed in 25 specimens of Akodon aff. arviculoides (2n = 24 and 25). NORs occurred on chromosome arms 2q, 3p, 6p, 7q and lOq, as identified by successive Ag- and G-band staining. In one specimen with 2n = 25, the supernumerary B chromosome presented Ag-NORs on both arms but in 3 other animals this chromosome was never stained. The number of Ag-NORs per cell ranged from 1 to 10 and the staining pattern was characteristic for each chromosome pair in an individual. No differences between tissues were observed in four animals investigated. © 1992 Taylor & Francis Group, LLC.